Strategi Pengembangan Objek Wisata Paralayang Batu dan Dampaknya Bagi Masyarakat Setempat - Rr Putriayu Niken Larasati; Suyeno; Langgeng Rahmatulllah Putra (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The development of the tourism sector is one of the efforts that can increase local income. Tourism development not only has an impact on the progress of tourism and its income but also has an impact on the State and surrounding communities so that the right strategy is important for tourism actors to be developed properly. This study seeks to find out and analyze related to the strategy of developing stone paragliding tourism objects and their impact on the local community so that for this the research used is a qualitative type with a descriptive analysis approach. The results obtained that the strategy used by paragliding tourism managers are three things which include: the development of tourism objects, promotion of tourism both offline and offline and involving the tourist community, and tourism business development involving businesses around paragliding tourism and the involvement of the local government, namely Batu City. While the resulting impact on the surrounding community includes: economic growth of the community so that the community has additional money or income, the creation of new jobs both for the main business or side business, additional foreign exchange for the State including the government and paragliding tourism managers, infrastructure development such as toilet roads etc. so that it can also be used for the community, and utilization for paragliding tourism business actors.